The apollo story man's journey to the moon - Moore, Patrick (United Kingdom : Revelation Films Ltd., 2009)
This is about the Apollo programme in fascinating detail, with access to unique NASA footage and the Science's Museum Space Expidition. from the launch pad disaster of the Apollo 1 mission, which lead to the tragic death's of three astronounts, to Armstrong's historical 'giant leap for mankind' and the Apollo 13 expolosion, where the world held its breath and prayed for the safety of those onboard.
Keywords: Project Apollo (U.S.).; Space flight to the moon